Assessment of relationship between retinopathy of prematurity severity and visual motor integration - Çelik, Gökhan; Kutlutürk, Seval (Effect Publishing Agency ( EPA ), 2021)
Aim: The aim of the current study is to assess the effects of retinopathy of prematurity (ROP) severity on visual motor integration in children. Material and Methods: Totally 104 children (44 girls, 60 boys) between 2 and 6 chronological age were included in the study. The children’s mean gestational age was 28.75±2.67 and birth weight was 1252.92±411.33. The Beery-Buktenica Developmental Test of Visual Motor Integration with supplemental tests of Visual Perception and Motor Coordination were used for the assessment of children. Results: The incidences of retinopathy of prematurity severity were 23.1% Stage 1+, 24% Stage 2+ and 52.9% Stage 3+ in the study. The incidence of abnormal visual motor integration was 51% of the study population. The incidence of abnormal visual perception and motor coordination were 37.5% and 51.9%, respectively. Referring to the Beery-Buktenica Developmental Test of Visual Motor Integration results, there was statistically significant correlation between the level of all visual motor integration, visual perception, and motor subtest results (p=0.00). There were not statistically significant correlation between retinopathy of prematurity severity and results of visual motor integration and visual perception tests (p>0.05). There was a significant correlation between retinopathy of prematurity severity and motor coordination test results (p<0.05). Conclusion: This study shows that as the retinopathy of prematurity severity increases, motor coordination skills are negatively affected in preterm born children at pre-school ages.

Amaç: Bu çalışmanın amacı, prematüre retinopatisi şiddeti ile çocukların görsel motor entegrasyon becerisi arasındaki ilişkisinin incelenmesidir. Materyal ve Metot: Çalışmaya, kronolojik yaşı 2 ile 6 yaş arasında toplam 104 çocuk (44 kız, 60 erkek) dahil edildi. Çocukların ortalama gebelik yaşı 28,75±2,67, doğum ağırlığı 1252,92±411,33’idi. Beery-Buktenica Gelişimsel Görsel Motor Entegrasyon testi ile Görsel Algı ve Motor Koordinasyon alt testleri kullanıldı. Bulgular: Çalışmada prematüre retinopatisinin şiddetine göre çocukların % 23,1’i Evre 1+, %24’ü Evre 2+ ve %52,9’u Evre 3+’idi. Anormal görsel motor entegrasyon insidansı çalışma popülasyonunun %51’idi. Anormal görsel algı ve motor koordinasyon insidansı sırasıyla % 37,5 ve %51,9’idi. Beery-Buktenica Gelişimsel Görsel Motor Entegrasyon Testi sonuçlarına göre, görsel motor entegrasyon, görsel algı ve motor koordinasyon alt test sonuçları arasında istatistiksel olarak anlamlı bir ilişki vardı (p=0,00). Prematüre retinopatisi şiddeti ile görsel motor entegrasyon ve görsel algı test sonuçları arasında istatistiksel olarak anlamlı ilişki yoktu (p>0,05). Prematüre retinopatisi şiddeti ile motor koordinasyon testi sonuçları arasında istatistiksel olarak anlamlı bir ilişki vardı (p<0,05). Sonuç: Bu çalışma, okul öncesi dönemdeki preterm doğumlu çocuklarda prematüre retinopatisinin şiddeti arttıkça, motor koordinasyon becerisinin olumsuz yönde etkilendiğini göstermektedir.
Prematüre retinopatisi şiddeti ile görsel motor entegrasyon arasındaki ilişkinin değerlendirilmesi
Keywords: Retinopathy of Prematurity; Visual-Motor Integration; Visual Perception; Motor Coordination; Prematüre Retinopatisi; Görsel Motor Entegrasyon; Görsel Algı; Motor Koordinasyon